Tips and Tricks to Improve Clinical and Aesthetic Outcomes in Latissimus Dorsi Flap Breast Reconstruction - Laporta, Rosaria; Sorotos, Michail; Longo, Benedetto; Santanelli di Pompeo, Fabio (Journal of Reconstructive Microsurgery, 2017)
Background The aim of this study is to present technical strategies to decrease donor-site complications, to optimize breast shaping, and to achieve symmetry in one-stage procedure in latissimus dorsi (LD) flap reconstruction.Methods Between 2004 and 2014, a retrospective review was performed on LD flap reconstructions. Demographics, reconstructive details, clinical and aesthetic outcomes were collected and analyzed. Patients were divided in historical control group (HCG) and new strategy group (NSG). In HCG, a horizontal/oblique LD skin paddle (SP) was drawn; only LD muscle was harvested for the implant pocket; and a contralateral symmetrization was planned without any algorithm. In NSG, a transverse LD-SP was centered on the middle to lower bra strap area; a double-layer muscle coverage was used to create the implant pocket; and a planning algorithm was developed to achieve symmetry.Results A total of 418 breast reconstructions were performed on 296 patients. The two groups were homogeneous regarding demographics, mastectomy weight, and implant volume (p > 0.05). No differences were observed in the incidence of a contralateral surgery, mean hospitalization time, and mastectomy skin flap and nipple–areola complex complications (p > 0.05), while surgical revision of the balancing procedure was more common in HCG than NSG (p = 0.001). Overall, donor-site morbidities occurred in 50 cases including 3 (1%) seroma in NSG and 17 (14.1%) in HCG, and 8 (2.7%) wound dehiscence in NSG and 18 (14.5%) in HCG (p = 0.001). Mean number of take backs to the operating room for secondary procedure was statistically significant between the groups in favor of NSG (p = 0.001).Conclusion Careful preoperative planning and adoption of appropriate reconstructive strategies can improve clinical and aesthetic outcomes in LD flap breast reconstruction at long-term follow-up.Level of Evidence This is a level III, therapeutic study.
Keywords: breast reconstruction; donor-site complications; LD flap; fat grafting; implant complications